2022
DOI: 10.3389/fimmu.2022.917232
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar macrophages in early stage COPD show functional deviations with properties of impaired immune activation

Abstract: Despite its high prevalence, the cellular and molecular mechanisms of chronic obstructive pulmonary disease (COPD) are far from being understood. Here, we determine disease-related changes in cellular and molecular compositions within the alveolar space and peripheral blood of a cohort of COPD patients and controls. Myeloid cells were the largest cellular compartment in the alveolar space with invading monocytes and proliferating macrophages elevated in COPD. Modeling cell-to-cell communication, signaling path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 103 publications
2
23
0
Order By: Relevance
“…One study found a decrease of CD16 expression and slight increase of CD14 expression on the surface of BAL cells from smokers and COPD patients, consistent with the CD14+ monocyte phenotype in our cohort (35). Intriguingly, using scRNA-seq, characterization of airspace monocytes which differentiate further into a number of macrophage phenotypes has also been described in patients with COVID-19 and COPD, confirming the connection between inflammation, disease, and recruited monocytes across multiple disease contexts (18,(37)(38)(39). We specifically identify CD93 as a novel marker for defining a disease-relevant population of airspace monocytes, enriched in smokers' airspaces.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…One study found a decrease of CD16 expression and slight increase of CD14 expression on the surface of BAL cells from smokers and COPD patients, consistent with the CD14+ monocyte phenotype in our cohort (35). Intriguingly, using scRNA-seq, characterization of airspace monocytes which differentiate further into a number of macrophage phenotypes has also been described in patients with COVID-19 and COPD, confirming the connection between inflammation, disease, and recruited monocytes across multiple disease contexts (18,(37)(38)(39). We specifically identify CD93 as a novel marker for defining a disease-relevant population of airspace monocytes, enriched in smokers' airspaces.…”
Section: Discussionsupporting
confidence: 88%
“…Both airspace monocytes and macrophages exhibited elevated expression of genes involved in phagocytosis and antigen processing/presentation as compared to blood monocytes from the same subjects (Figure 1G and Figure S3B), supporting the interpretation that airspace monocytes are a differentiating cell population. As external support from a separate human disease cohort, we compared our airspace monocyte population against work from Baβler et al ( 18 ), who identified a population of monocytes differentiating into macrophages that was enriched in BAL samples from smokers with chronic obstructive pulmonary disease (COPD). Our smoking-associated airspace monocytes strongly and specifically expressed markers from a population of differentiating monocytes (i.e., elevated compared to blood-derived monocytes and AM alike) identified in Baβler et al, further supporting that airspace monocytes accumulate in smokers and may serve as precursors to other tissue macrophage states (Figure S3C-E).…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that the heterogeneity of macrophages and the activation of T cells are dependent on external stimuli and the microenvironment [ 68 ]. Several factors, including smoking status, severity of COPD, acute exacerbations, and corticosteroid use, may contribute to different conclusions [ 69 , 70 , 71 ]. Additionally, in the validation dataset, the degree of neutrophil infiltration was enhanced in lung tissue samples from COPD patients, which has been extensively demonstrated in previous studies [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic obstructive pulmonary disease (COPD) is associated with persistent macrophage infiltration in the lung parenchyma and alveolar space even after smoking cessation ( 1 ), which correlates with disease severity and areas of lung destruction ( 2 ). Macrophages isolated from BAL in COPD are derived from both tissue-resident macrophages with the capacity for self-renewal and circulating peripheral blood monocytes that migrate to the lung under a variety of stimuli ( 3 , 4 ). Despite the increased abundance of airway and alveolar macrophages (hereafter termed alveolar macrophages [AMs]) in COPD, recurrent respiratory infections are abundant, accelerating disease progression and mortality ( 5 ).…”
mentioning
confidence: 99%
“…For example, stimulated bone marrow–derived macrophages predominantly use glycolysis ( 11 ) to rapidly generate ATP for proinflammatory effector functions, whereas AMs that inhabit a low-glucose, high-lipid environment in the healthy lung rely on OXPHOS to meet energy demands ( 12 , 13 ). AMs from individuals with COPD display a defect in mitochondrial respiration ( 10 , 13 ), with lower compensatory glycolysis and alterations in metabolite abundance ( 4 , 12 ). Yet how this metabolic rewiring relates to the functional capacity of AMs and whether this phenomenon can be therapeutically reversed with beneficial effects had yet to be defined.…”
mentioning
confidence: 99%